Supply Chain Design for Global Competitiveness - Jie, Ferry (Proceeding International Conference on Science and Engineering, 2017)
A supply chain consists of the flow of products and services from raw materials manufacturers, component and intermediate manufacturers, final product manufacturers, wholesalers, distributors and retailers. All are connected by transportation, storage activities, and integrated through information, planning, and integration activities. Many large firms are moving away from in-house Vertically Integrated structures to Supply Chain Management. Supply Chain are the planning and management of all activities involved in sourcing and procurement, conversion, and all logistics management activities. It also includes coordination with channel partners, which can be suppliers, intermediaries, third party service providers, and customers. Supply chain management is the design of seamless value added processes across organization boundaries to meet the real needs of the end customer. Failure to proactively design a SC results in poor coordination of effort, incompatible information systems, long cycle times, communication problems, customer service issues, excessive waste and environmental degradation, relatively high inventories for the level of customer service achieved, and lower the optimal profit. A process map is a graphic representation of the system and contains a sequence of steps that are performed to produce some desired output. The primary goal behind process mapping is to make complex systems visible. The logistics/supply chain design and technology decision is of great strategic importance to logistics, the firm as a whole, and the supply chain. A number of factors may suggest the need to design the logistics/supply chain. A formal, structured process for design and digital tools is preferable; the potential impacts on cost and service justify a significant effort toward following a sound process. Numerous factors including technology may affect the design of a logistics and supply chain and the location of specific facilities within the context of the network.